Efektivitas Guru Pendamping dalam Proses Pembelajaran di Taman Kanak-Kanak Aisyiah Bustanul Athfal Tulaan, Kecamatan Gunung Meriah, Kabupaten Aceh Singkil - Intan Triana; Khadijah Khadijah; Sri Wahyuni (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
An effective accompanying teacher can carry out his duties and functions professionally. Accompanying teachers are teachers who accompany children while studying in class. The accompanying teacher acts as a bridge in interacting between the core teacher and children who generally still have difficulty concentrating and focusing on paying attention to the core teacher. Because apart from being a therapist, he also helps the main teacher in providing lessons. The aim of this research is to find out how the accompanying teacher program works in the learning planning process at Aisyiyah Bustanul Athfal Tulaan Kindergarten, to find out how effective the accompanying teacher program is in the learning process at Aisyiyah Bustanul Athfal Kindergarten, Tula'an village before there are accompanying teachers, to find out how the process works. learning at Aisyiyah Bustanul Athfal Tulaan Kindergarten. The subjects in this research involved accompanying teachers, core teachers and school principals. This type of research is descriptive qualitative, researchers collect data through observation, interviews and documentation. The results of the research show in 3 aspects, namely: The accompanying teacher program in assisting the learning process at Ik Aisyiyah Bustanul Athfal Tulaan is good at assisting with lesson plans (RPP) and assisting in creating learning ideas. The effectiveness program for accompanying teachers in the learning process at Aisyiyah Bustanul Atfal Tulaan Kindergarten has been effective and good. And the learning process at Aisyiah Bustanul Athfal Tulaan Kindergarten is very good, accompanying teachers help children in many ways, such as children's concentration, participation in class, socialization, being polite and controlling children's behavior.